KAJIAN ZONASI BAHAYA ERUPSI GUNUNG TALANG TERHADAP PENGGUNAAN LAHAN DI KABUPATEN SOLOK - Diah Permata Sari; Helfia Edial (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
The purpose of this research is to know the eruption prone area of Mount Talang eruption, to know the social and economic vulnerability to eruption hazards, to know the eruption zoning, and to determine the feasibility of space allocation based on eruption hazard zoning. In this study data analysis technique used is GIS analysis, namely buffering, image processing, scoring, overlays, dan matching. The results of this study indicate the Disaster-Prone Areas III covers an area of 336 Ha with a radius 2 km from the central ctarer, Disaster-Prone Areas II covers 5923 Ha with a radius of 5 km, and Disaster-Prone Areas I covers 3356 Ha with a radius of 8 km. For social vulnerability to eruption in the study area included in the low class. And based on the results of the ruption zoning analysis there are four nagari (4) including into high hazard zones in three districts (3), fifteen nagari (15) including into moderate hazard zoning in three sub-districts (3), and eleven nagari (11) including into low hazard zoning in three districts (3). Seattlemens, gardens/ plantations in high hazard zones are not suitable for spatial use, and industries in the medium zone are also categorized as not suitable for space use.